2014
DOI: 10.20510/ukjpb/2/i6/91174
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro trial to study the effect of inclusion of different levels of coconut oil on sheep rumen methanogenesis and fermentation processes

Abstract: An in vitro trial was conducted in fermentation vessels under anaerobic conditions using composite feed-1 and composite feed-2 with inclusion of different levels of Coconut Oil (CO) along with buffered rumen liquor of sheep to observe the effects of oil on rumen methanogenesis and fermentation. The Composite Feed-1(CF-1) consisted of 40% of concentrate and Composite Feed-2 (CF-2) had 25 % of concentrate. The different levels of CO used were 0.5,1 and 2 µl/ml. Among the gas production and methane concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Results from the present in vitro study indicated that the silkworm pupae oil supplementation decreased total gas, methane production, and rumen protozoal population. Similar to the present results, a linear decrease in total gas production was reported with graded supplementation of coconut oil [23]. Pilajun and Wanapat [24] reported that supplementation of coconut and almond oil either alone (5%) or combination (50:50) at 5% with variable roughage and concentrate ratio revealed variable response on gas production.…”
Section: Discussionsupporting
confidence: 90%
“…Results from the present in vitro study indicated that the silkworm pupae oil supplementation decreased total gas, methane production, and rumen protozoal population. Similar to the present results, a linear decrease in total gas production was reported with graded supplementation of coconut oil [23]. Pilajun and Wanapat [24] reported that supplementation of coconut and almond oil either alone (5%) or combination (50:50) at 5% with variable roughage and concentrate ratio revealed variable response on gas production.…”
Section: Discussionsupporting
confidence: 90%